A review on natural and synthetic polymers employed in the formulation of oral disintegrating tablets - Madhulika, G.S.S.V.; Ramya Kuber, B. (Journal of Drug Delivery and Therapeutics, 2019)
The oral route is the most popular route of administration for numerous drugs because it is considered as a safest, most preferred and less economical. Disintegrating agents are the substances that disperse or dissolve within a matter of seconds. This disintegrating mechanism helps in dysphagia, pediatric and geriatric patients. Synthetic disintegrating agents are available as a highly economical and less effective when compared to natural disintegrating agents. Therefore natural disintegrants serve as the best alternative to overcome the problems of these synthetic substances. Due to their numerous advantages over synthetic products they are widely used in the pharmaceutical field as a binder, disintegrants, gums, and mucilages. Keywords: Disintegrants, dysphagia, synthetic substances.